Peripheral clocks and systemic zeitgeber interactions: from molecular mechanisms to circadian precision medicine - Bautista, Jhommara; Ojeda-Mosquera, Sofía; Ordóñez-Lozada, Dylan; López-Cortés, Andrés (Frontiers in Endocrinology, 2025)
Circadian rhythms orchestrate nearly every aspect of human physiology through a hierarchical network of clocks. While the suprachiasmatic nucleus (SCN) serves as the central pacemaker, peripheral clocks within the brain, heart, liver, gut, pancreas, adipose tissue, adrenal glands, lungs, and skeletal muscle independently regulate organ-specific functions. These autonomous oscillators, governed by transcriptional–translational feedback loops of core clock genes, align with environmental and physiological zeitgebers such as light, feeding, temperature, and hormones. Disruption of this temporal organization—through shift work, genetic alterations, or lifestyle factors—drives systemic misalignment, contributing to metabolic disease, cardiovascular dysfunction, neurodegeneration, cancer, and immune imbalance. This review explores the molecular mechanisms and physiological roles of peripheral clocks across organ systems, emphasizing their interplay with the SCN and zeitgebers. We also highlight emerging chronotherapeutic strategies that exploit circadian biology to optimize treatment outcomes. Understanding inter-organ circadian communication is key to unlocking personalized interventions and restoring systemic rhythmicity for health.